OPTIMALISASI PROSEDUR ENCLOSED SPACE ENTRY GUNA MENINGKATKAN KESELAMATAN CREW DI MT. ALFA ALANDIA - Muhammad Rezki Rozadinata; Achmad Ali Mashartanto; Bayu Yudho Baskoro; Syafni Yelvi Siska; I Kadek Laju (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Muhammad Rezki Rozadinata, NIT 113307221071 (2026), “Optimization of Enclosed Space Entry Procedures to Improve Crew Safety on MT. ALFA ALANDIA”. Supervised by Mr. Achmad Ali Mashartanto, S.Kom., M.Si and Mrs. Syafni Yelvi Siska, M.Pd. This study aims to optimize the enclosed space entry procedure in order to improve crew safety on board MT. Alfa Alandia. The background of this research is based on the existence of non-compliance in the implementation of safety proce- dures when entering enclosed spaces, such as the crew’s lack of understanding of toxic gas hazards, suboptimal use of personal protective equipment (PPE), and in- adequate supervision. These conditions have the potential to cause serious, even fatal, work accidents. The research method used is a descriptive qualitative method with a de- scriptive approach. The informants in this study consist of the Captain, Chief Of- ficer, Pumpman, and several crew members directly involved in enclosed space en- try activities. Data collection techniques were carried out through direct onboard observation, in-depth interviews with informants, and documentation related to procedures and work implementation. The data analysis technique used an inter- active analysis model consisting of data reduction, data display, and conclusion drawing. The results show that the crew’s understanding of enclosed space entry pro- cedures is still uneven, and several procedural steps are not consistently imple- mented, such as atmospheric testing and completion of the Permit to work. There- fore, optimization is required through enhanced training and safety drills, stricter supervision, and enforcement of safety procedures in accordance with international standards such as ISGOTT. With this optimization, it is expected that the level of crew safety when working in enclosed spaces can be significantly improved.